MSL1 is a mechanosensitive ion channel that dissipates mitochondrial membrane potential and maintains redox homeostasis in mitochondria during abiotic stress - Lee, Chunpong; Maksaev, Grigory; Jensen, Gregory S.; Murcha, Monika W.; Wilson, Margaret E.; Fricker, Mark; Hell, Rüdiger; Haswell, Elizabeth S.; Millar, A. Harvey; Sweetlove, Lee J. (The plant journal, 2016)
Mitochondria must maintain tight control over the electrochemical gradient across their inner membrane to allow ATP synthesis while maintaining a redox-balanced electron transport chain and avoiding excessive reactive oxygen species production. However, there is a scarcity of knowledge about the ion transporters in the inner mitochondrial membrane that contribute to control of membrane potential. We show that loss of MSL1, a member of a family of mechanosensitive ion channels related to the bacterial channel MscS, leads to increased membrane potential of Arabidopsis mitochondria under specific bioenergetic states. We demonstrate that MSL1 localises to the inner mitochondrial membrane. When expressed in Escherichia coli, MSL1 forms a stretch-activated ion channel with a slight preference for anions and provides protection against hypo-osmotic shock. In contrast, loss of MSL1 in Arabidopsis did not prevent swelling of isolated mitochondria in hypo-osmotic conditions. Instead, our data suggest that ion transport by MSL1 leads to dissipation of mitochondrial membrane potential when it becomes too high. The importance of MSL1 function was demonstrated by the observation of a higher oxidation state of the mitochondrial glutathione pool in msl1-1 mutants under moderate heat- and heavy-metal-stress. Furthermore, we show that MSL1 function is not directly implicated in mitochondrial membrane potential pulsing, but is complementary and appears to be important under similar conditions.